2013
DOI: 10.26786/1920-7603(2013)8
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency in pollen foraging by honey bees: Time, motion and pollen depletion on flowers of <i>Sisyrinchium palmifolium</i> Linnaeus (Asparagales: Iridaceae)

Abstract: Honey bees depend on flower resources (nectar and pollen) to supply individual and colony needs. Although behavioural studies already assessed optimum foraging patterns of bumblebees, honey bees foraging behavioural patterns have been poorly assessed. We used Sysirinchium palmifolium L. (Iridaceae), a low-growing, abundant and anthophilous grassland flower to test the hypotheses that Apis mellifera workers would i) spend more time, ii) visit a greater number of flowers, and iii) travel greater distances within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…This behaviour was reported for the small bodies' bee, as compared to their large size counterparts (Tangmitcharoen et al, 2006). The difference in time spent between the flowervisiting insects could be due to the depleted pollen grains in the already exploited flowers (Silva et al, 2013). In present study, Halictidae 1 and H. itama were found to spent longer time as compared to other visitors, as these 2 insect taxa were often observed foraging at the flowers in the early morning, much earlier than the other insect visitors.…”
Section: Visitation Behaviour Of the Flower-visiting Insectssupporting
confidence: 56%
“…This behaviour was reported for the small bodies' bee, as compared to their large size counterparts (Tangmitcharoen et al, 2006). The difference in time spent between the flowervisiting insects could be due to the depleted pollen grains in the already exploited flowers (Silva et al, 2013). In present study, Halictidae 1 and H. itama were found to spent longer time as compared to other visitors, as these 2 insect taxa were often observed foraging at the flowers in the early morning, much earlier than the other insect visitors.…”
Section: Visitation Behaviour Of the Flower-visiting Insectssupporting
confidence: 56%
“…Kajobe and Echazarreta (2005) found that stingless bees' activities were optimal at 78% of relative humidity. Indeed, high humidity leads to a dilution of nectar and a disruption of the physical properties of pollen (Alves et al, 2015; Silva et al, 2013) which resulted in less attractiveness of the honey bees to the flower rewards. Periods of rainfall in addition to be positively correlated with relative humidity, make foraging activities almost impossible (De Mattos et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In a nearby area with no A. gerrardii trees, Abou-Shaara, Al-Ghamdi and Mohamed [23] reported foraging activities of 73 and 43 workers/colony/5 min, which were less than the 109 and 49 workers/colony/3 min found in the present study for native and imported colonies, respectively, confirming the effect of the nectar-rich Acacia flow in this study. Additionally, Silva, et al [44] suggested that the field trips of foraging honeybees may peak at the time of the day when abundant food resources are accessible.…”
Section: Discussionmentioning
confidence: 99%